Teniso ir padelio žaidimu veiklos analize bei charakteringi bruožai - Šakinis, D.; Paulauskas, R. (Sporto Mokslas-Sport Science, 2025)
The aim of this study was to investigate and compare the physical load experienced during tennis and padel matches. Eight national-level male tennis players (n = 8; age: 27.0 ± 7.4 years; height: 186.3 ± 7.7 cm; body mass: 81.5 ± 10.7 kg) participated in the study. All participants held official rankings from the National Tennis Association and regularly competed in major national singles and doubles tournaments. Additionally, they had experience participating in A-level padel tournaments organized by the National Padel Federation. A total of 12 simulated matches were conducted - six in tennis and six in padel. Players were paired based on similar skill levels to ensure competitive balance. Each participant played three matches in each sport, with each match lasting 40 minutes to simulate the duration of one set. We compared the physical loads experienced in tennis and padel doubles and identified a distinct characteristics of game activity in both sports. The results indicated that tennis imposed a significantly greater external physical load across all measured parameters. Total distance covered, movement intensity, average and maximum speed, number of sprints, and distance covered during high-intensity accelerations were all higher in tennis than in padel. However, heart rate and blood lactate levels did not significantly differ between the two sports.